Instant Apache Camel message routing - Ibryam, Bilgin (Packt Publishing, 2013)
Filled with practical, step-by-step instructions and clear explanations for the most important and useful tasks. This short, instruction-based guide shows you how to perform application integration using the industry standard Enterprise Integration Patterns. This book is intended for Java developers who are new to Apache Camel and message- oriented applications.